Parasites in bloom: flowers aid dispersal and transmission of pollinator parasites within and between bee species - Graystock,P; Goulson,D; Hughes,WOH (Proceedings of the Royal Society B: Biological Sciences, 2015)
The dispersal of parasites is critical for epidemiology, and the interspecific vectoring of parasites when species share resources may play an underappreciated role in parasite dispersal. One of the best examples of such a situation is the shared use of flowers by pollinators, but the importance of flowers and interspecific vectoring in the dispersal of pollinator parasites is poorly understood and frequently overlooked. Here, we use an experimental approach to show that during even short foraging periods of 3 h, three bumblebee parasites and two honeybee parasites were dispersed effectively onto flowers by their hosts, and then vectored readily between flowers by non-host pollinator species. The results suggest that flowers are likely to be hotspots for the transmission of pollinator parasites and that considering potential vector, as well as host, species will be of general importance for understanding the distribution and transmission of parasites in the environment and between pollinators.